2018
DOI: 10.1186/s13068-018-1012-4
|View full text |Cite
|
Sign up to set email alerts
|

Organic acid production from potato starch waste fermentation by rumen microbial communities from Dutch and Thai dairy cows

Abstract: BackgroundExploring different microbial sources for biotechnological production of organic acids is important. Dutch and Thai cow rumen samples were used as inocula to produce organic acid from starch waste in anaerobic reactors. Organic acid production profiles were determined and microbial communities were compared using 16S ribosomal ribonucleic acid gene amplicon pyrosequencing.ResultsIn both reactors, lactate was the main initial product and was associated with growth of Streptococcus spp. (86% average re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…1a, and the major bands are assigned in Table 1 [19]. The fingerprint region (1600–1000 cm −1 ) in the spectra of alkali lignin significantly changed after laccase and LMS treatment, corresponding to the stretching vibrations of the different groups in lignin [20]. This suggested that the overall structure of alkali lignin had been destroyed, to some extent, after laccase and LMS pretreatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a, and the major bands are assigned in Table 1 [19]. The fingerprint region (1600–1000 cm −1 ) in the spectra of alkali lignin significantly changed after laccase and LMS treatment, corresponding to the stretching vibrations of the different groups in lignin [20]. This suggested that the overall structure of alkali lignin had been destroyed, to some extent, after laccase and LMS pretreatment.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of the peak at 1267 cm −1 changed slightly after laccase pretreatment, which suggested that the carbonyl in guaiacyl was ruptured during the pretreatment. The signal intensity of alkali lignin at 1633 cm −1 increased after LMS pretreatment, this indicated the formation of small molecule lignin in the LMS pretreatment [20].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Associations between Pseudoramibacter and ruminant feed efficiency ( Table 3 ) are not well reported in the literature. Pseudoramibacter is a member of the Eubacteriaceae family and can utilize carbohydrates for energy ( Deusch et al, 2017 ), while producing fermentation end products butyrate, acetate, formate, and hydrogen ( Deusch et al, 2017 ; Palakawong Na Ayudthaya et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…was significantly increased under 3 g L -1 COS treatments ( Supplementary Figure S6 ). Members of the phylum Bacteroidetes , including genus Parabacteroides , participated in provisioning the host with energy harvested through the fermentation of indigestible polysaccharides to produce SCFAs ( Johnson et al, 2017 ), and were also related to butyrate production ( Palakawong Na Ayudthaya et al, 2018 ). Moreover, colonic hydrogen concentration in rats was positively correlated with the abundance of genus Parabacteroides ( Nishimura et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%